Immunological Impact of Calprotectin and Interleukin-34 in Immunocompromised Patients with Chronic Cytomegalovirus Infection - Hama_Salim, Honya; Babakir-Mina, Muhammed (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Cytomegalovirus (CMV) causes the most prevalent and severe opportunistic infection in immunocompromised patients following solid organ or hematopoietic stem cell transplantation, with the highest morbidity and mortality rates among herpesviruses. The study objective was to compare and determine the CMV chronic infection and related hematological and immunological markers in immunodeficient and immunocompetent participants. A prospective case–control study among 85 participants was designed to measure CMV-immunoglobulin G (IgG) and to evaluate interleukin-34 and serum calprotectin as biomarkers; total leukocyte, granulocyte, lymphocyte, and platelet counts were also measured following blood collection. A high CMV IgG positivity was observed across all groups in this investigation, indicating widespread chronic infection. CMV IgG, interleukin-34 (IL-34), and calprotectin levels did not differ significantly between immunocompetent and immunocompromised individuals. There was no significant association between CMV IgG and IL-34 or serum calprotectin. Furthermore, IL-34 showed a significantly higher mean in males compared to females (p = 0.002). An exploratory observation was that IL-34 had a moderate positive correlation with serum calprotectin (ρ = 0.609, 95% confidence interval: 0.450–0.731, p < 0.001) across all study participants. The study findings call for more research to elucidate the clinical roles of calprotectin and IL-34 in immunocompromised patients.